2023
DOI: 10.1186/s40813-022-00301-x
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography as a possible technique for the estimation of parturition onset in sows

Abstract: Background This study explores the possibility of using infrared thermography to estimate the onset of parturition in sows. Infrared camera (IRC) and infrared laser thermometer (IRT) were used to obtain the auricular skin temperature of sows along with rectal temperatures, from approximately one week before the anticipated farrowing until 24 h post-partum. Three commercial piglet producing farms were included in the study. Results There were large … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…(2) Pertaining to temperature prediction, a random forest algorithm, optimized by an adaptive genetic algorithm, constructs an inversion model based on environmental parameters, vulvar temperature, and rectal temperature, aspiring to predict the sows' temperature accurately. (3) In the context of practical farming, test results exhibit that the sow temperature monitoring method posited in this study can accurately predict the rectal temperature of sows in sheltered scenarios, thereby establishing a foundation for health monitoring and estrus detection in sows.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…(2) Pertaining to temperature prediction, a random forest algorithm, optimized by an adaptive genetic algorithm, constructs an inversion model based on environmental parameters, vulvar temperature, and rectal temperature, aspiring to predict the sows' temperature accurately. (3) In the context of practical farming, test results exhibit that the sow temperature monitoring method posited in this study can accurately predict the rectal temperature of sows in sheltered scenarios, thereby establishing a foundation for health monitoring and estrus detection in sows.…”
Section: Introductionmentioning
confidence: 89%
“…In light of the rapid advancement of automated temperature measurement technology, infrared thermography (IRT) imaging technology is progressively applied in large-scale sow management. Currently, researchers have embarked on studies related to sow lameness detection, farrowing prediction, febrile pig detection, metabolic function assessment in pigs, and early shoulder sore identification in sows, utilizing IRT imaging technology [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Preparturient sows also experience changes in thermoregulation and cardiovascular changes. A number of authors have reported an increase in rectal temperature (0.5–1.4°C) or skin temperature in the 12 h before farrowing (Gulliksen et al, 2023; Hendrix et al, 1978; Vermeer & van der Wilt, 1999), indicating increased heat production. In the same period, heart rate and respiratory rate also increase considerably (Gulliksen et al, 2023; Hendrix et al, 1978).…”
Section: Peri‐partum Physiology and Issuesmentioning
confidence: 99%
“…A number of authors have reported an increase in rectal temperature (0.5–1.4°C) or skin temperature in the 12 h before farrowing (Gulliksen et al, 2023; Hendrix et al, 1978; Vermeer & van der Wilt, 1999), indicating increased heat production. In the same period, heart rate and respiratory rate also increase considerably (Gulliksen et al, 2023; Hendrix et al, 1978). It is not clear what these changes reflect, although they may be related to the increased activity of the sow, with heat production associated with colostrum production (Theil et al, 2022), or possibly with the increase in uterine contractions in this period.…”
Section: Peri‐partum Physiology and Issuesmentioning
confidence: 99%
“…The BCT can be used as a hint for several diseases or hormonal changes, such as mastitis, metritis, and agalactia (MMA) [12], the onset of farrowing in sows [13], or, for example, classical fever in fattening pigs [1]. Further, thermal images were used to detect inflammation [14] and lesions [15], which are linked to isolated surface temperature deviations.…”
Section: Introductionmentioning
confidence: 99%